Strengthening the parent-child relationship in therapy : laying the foundation for healthy development - Niec, Larissa N. (American Psychological Association, 2022)
"This book integrates the basic and applied literature to provide mental health providers with concrete, evidence-based strategies for building and strengthening the parent-child relationship and addresses challenges typically neglected by intervention manuals"--